Etiology and mechanisms of ulnar and median forearm nerve injuries - Puzović Vladimir; Samardžić Miroslav; Jovanović Milan; Živković Bojana; Savić Andrija; Rasulić Lukas (Vojnosanitetski Pregled)
Bacgraund/Aim. Most often injuries of brachial plexus and its branches disable the injured from using their arms and/or hands. The aim of this study was to investigate the etiology and mechanisms of median and ulnar forearm nerves injuries. Methods. This retrospective cohort study included 99 patients surgically treated in the Clinic of Neurosurgery, Clinical Center of Serbia, from January 1st, 2000 to December 31st, 2010. All data are obtained from the patients' histories. Results. The majority of the injured patients were male, 81 (81.8%), while only 18 (18.2%) were females, both mainly with nerve injuries of the distal forearm - 75 (75.6%). Two injury mechanisms were present, transection in 85 patients and traction and contusion in 14 of the patients. The most frequent etiological factor of nerve injuries was cutting, in 61 of the patients. Nerve injuries are often associated with other injuries. In the studied patients there were 22 vascular injuries, 33 muscle and tendon injuries and 20 bone fractures. Conclusion. The majority of those patients with peripheral nerve injuries are represented in the working age population, which is a major socioeconomic problem. In our study 66 out of 99 patients were between 17 and 40 years old, in the most productive age. The fact that the majority of patients had nerve injuries of the distal forearm and that they are operated within the first 6 months after injury, promises them good functional prognosis.